Emilia Pardo Bazán, the First Theoretician and Critic of Rexurdimento - Angueira, Anxo (Madrygal. Revista de Estudios Gallegos, 2023)
Especially during the 1880-1890 decade, Emilia Pardo Bazán carried out an intense theoretical and critical activity, both in Spanish literature and in the emerging literature in Galician language. She was the first author to theoretically address the idea of renaissance applied to the Galician reality of those years and also the first one to make a critical analysis of the most relevant authors of that period: Rosalía de Castro, Manuel Curros Enríquez, Eduardo Pondal and Valentín Lamas Carvajal. She was largely responsible for the introduction of Michelet’s paradigm, with which she made comparisons between the Galician “renaissance” called “Rexurdimento” and the Catalan “renaixença”. She studied the great works and authors of this period and the impact of his critiques was very considerable, both for the purpose of setting interpretive directions in later literary histories, and for creating important controversy and even provoking critical responses in literary format such as O divino sainete. This type of intervention by our author needs to be placed in the context of disputes where the literary is mixed with the ideological and ultimately in the open struggle for the incipient symbolic capital.